Diagnostic Accuracy of Computed Tomography in the Pre-Operative Evaluation of Posterior Fossa Tumours in Children - Sarker, Taposhi; Sarker, Robindra Nath; Rabbi, Akanda Fazle; Das, Kanta; Hossain, Ahmed (Journal of Dhaka Medical College, 2013)
J Dhaka Medical College, Vol. 21, No. 2, October, 2012, Page 188-196 DOI: http://dx.doi.org/10.3329/jdmc.v21i2.15357